Korelasi Sebaran Temperatur Permukaan Dengan Anomali Geofiska Pada Gunung Api Lokon - Bujung, Cyrke; Makahinda, Tineke; Lubis, Muhammad Rizky (Universitas Negeri Manado, 2020)
ABSTRACT. Lokon Volcano is one of 129 active volcanoes in Indonesia that often erupts. The purpose of this study was to determine how the distribution of the surface temperature of the volcano using the Data Image for the period of May 2017, and to find out how the temperature distribution correlates with geomagnetic anomalies. Image data taken at USGS will be processed at Ilwiss software and will describe the surface temperature of the lokon volcano. Geomagnetic data taken from PVMBG illustrates geomagnetic anomalies in the locon volcano. The research results show that the surface of the lokon volcano has a temperature value ranging from 20Ëš - 36Ëš C. Correlation of temperature distribution with geomagnetic locon volcano data shows the existence of geomagnetic anomalies where there is a smaller geomagnetic anomaly value indicating a lower temperature value. while the low Anomaly value indicates a heat source.Â Keywords : Correlations, Surface Temperature, Geomagnetic Anomaly.